Development of Modern Technologies – Is the Basis of a Sustainable Economy? - Andronaty N. R. (Problems of the Regional Energetics)
The significance of the problem of providing technological assurance of processes is demonstrated based on examination of the development of computer technology in Moldova. Only human potential availability of well trained professionals, logistics and coordination of the whole process of the work cycle from research to production can provide a high level of quality, contribute to promoting and ensuring market competitiveness of manufactured products. It is demonstrated that there are many areas that require the use of computer systems, including analog and digital specialized electronic machines. Providing conditions for the evolution of new technologies and their development is the most important prerequisite for sustainable economic development.